2020
DOI: 10.1051/0004-6361/201937334
|View full text |Cite
|
Sign up to set email alerts
|

A multiplicity study of transiting exoplanet host stars

Abstract: Context. Binarity is a widespread phenomenon around solar-type stars, including the host stars of transiting extrasolar planets. Aims. We performed a detailed study of six transiting planetary systems with relatively bright stars close enough to affect observations of these systems. These contaminants were characterised in a companion work. Methods. We used theoretical spectra to propagate the observed K-band light ratios into the optical passbands used to observe these systems. Light curves were analysed whil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 76 publications
9
37
0
Order By: Relevance
“…Here we present an analysis of the transmission and emission spectra of WASP-76 b, taken with the WFC3 G141 grism aboard HST. Although not reported in the discovery paper (West et al 2016), the presence of a stellar companion was noted in several studies (Wöllert & Brandner 2015;Ginski et al 2016;Ngo et al 2016;Bohn et al 2020) and the common proper motion of the two objects was confirmed by Southworth et al (2020). This was not accounted for in previous WFC3 transmission studies and, using Wayne simulations (Varley et al 2017), we show that this companion affects the spectral data obtained.…”
Section: Introductionmentioning
confidence: 43%
See 1 more Smart Citation
“…Here we present an analysis of the transmission and emission spectra of WASP-76 b, taken with the WFC3 G141 grism aboard HST. Although not reported in the discovery paper (West et al 2016), the presence of a stellar companion was noted in several studies (Wöllert & Brandner 2015;Ginski et al 2016;Ngo et al 2016;Bohn et al 2020) and the common proper motion of the two objects was confirmed by Southworth et al (2020). This was not accounted for in previous WFC3 transmission studies and, using Wayne simulations (Varley et al 2017), we show that this companion affects the spectral data obtained.…”
Section: Introductionmentioning
confidence: 43%
“…The stellar companion of WASP-76, reported by Bohn et al (2020) and Southworth et al (2020) has a K magnitude which is ∼2.30 fainter and the separation between both stars is only 0 436. As such, it is expected to have contaminated the transmission and emission spectra obtained by Hubble.…”
Section: Removal Of Companion Contaminationmentioning
confidence: 90%
“…We complemented the multiplicity data from these databases with the Catalogue of Exoplanets in Binary Star Systems 5 (Schwarz et al, 2016). We added to this all systems from published surveys searching for visual stellar companions to circumprimary planetary systems (Luhman and Jayawardhana, 2002;Patience et al, 2002;Udry et al, 2004;Mugrauer et al, 2006;Mugrauer et al, 2007a;Mugrauer et al, 2007b;Raghavan et al, 2006;, Eggenberger et al, 2011Daemgen et al, 2009;Mugrauer and Neuhäuser, 2009;Adams et al, 2012;Adams et al, 2013;Ginski et al, 2012, Ginski et al, 2016Ginski et al, 2020;Lillo-Box et al, 2012;Bergfors et al, 2013;Faedi et al, 2013;Lodieu et al, 2014;Wang et al, 2014;Mugrauer and Ginski, 2015;Wöllert et al, 2015;Deacon et al, 2016;Kraus et al, 2016;Ngo et al, 2016;Ngo et al, 2017;Furlan et al, 2017;Moutou et al, 2017;Coker et al, 2018;Dietrich and Ginski, 2018;Ziegler et al, 2018;Fontanive et al, 2019;Mugrauer, 2019;Bohn et al, 2020;Southworth et al, 2020) or reviews of planets in binaries (Bonavita and Desidera, 2007;Bonavita and Desidera, 2020;…”
Section: Binaries In Surveys and The Literaturementioning
confidence: 99%
“…We also note that WASP-30b is not a planetary system, but a stellar binary, with a near main-sequence F8 primary and a 61 M J secondary, that can be classified as a brown dwarf. Because there is no mass entry in TIC for WASP-20, we relied on the analysis of Southworth et al (2020). WASP-20 is a binary, and the stellar parameters correspond to the brighter companion.…”
Section: Discussionmentioning
confidence: 99%